Eosinophilic esophagitis. What diet? How to treat it? The point of view of a gastroenterologist working in a department of allergology - Andrzej Kuźmiński; Michał Przybyszewski; Justyna Przybyszewska; Zbigniew Bartuzi (Gastroenterology Review)
Eosinophilic esophagitis (EoE) belongs to a broad group of allergic gastrointestinal diseases. More narrowly, it is classified as an eosinophilic gastrointestinal disease and is its most common representative. Until recently, this disease was extremely rare, but the last 3 decades have seen a rapid increase in its prevalence to such an extent that in some recent studies it has been named the most common esophageal disease after reflux disease. EoE is an interdisciplinary disorder on the borderline between gastrointestinal and allergologic diseases, requiring cooperation of these two branches of medicine in diagnostics and treatment. Despite the development of medical science it remains a poorly known disease, difficult to diagnose and even more difficult to treat. Recent years have seen the emergence of new studies and guidelines, both American and European, that have radically changed our approach to the diagnosis and treatment of EoE.